Management of Post- Partum Pulmonary Edema in an Intensive Care Unit of a Peripheral District Hospital: A Case Report - Bijukchhe, Satish; Bidari, Prashant; Kumar Silwal, Ishwor; Babu Lamichhane, Subash; Subedi, Rupak; Adhikari, Samikshya (Nepal Journal of Health Sciences, 2026)
Pulmonary edema is an infrequent yet severe complication that may arise in the postpartum period following normal vaginal delivery. Prompt recognition and treatment are essential to prevent further deterioration. Here, we present a case involving a 23-year-old primigravida, who exhibited symptoms of shortness of breath, cough, abdominal pain, and orthopnea on the fifth day after childbirth. Following diagnosis of postpartum pulmonary edema, the patient received subsequent management in the Intensive Care Unit (ICU) of a Peripheral hospital. The patient's clinical condition improved, leading to discharge from the ICU on the eighth day postpartum. This case underscores the significance of coordinated care across various medical specialties and timely intervention in managing such conditions even in resource limited setting.